Higgs physics in/beyond the standard model and effective theories in cosmology. (2019)
Inflation has become a paradigm in science, allowing us to describe the first moments of the Universe and the implications for the later formation of the large-scale structures. This mechanism requires, in most of its implementations, a scalar field to drive the primordial accelerated expansion, which in turn, via its quantum fluctuations, can generate irregularities in the energy density after horizon exit which, afterwards, will generate the large-scale structure just because of gravitational instability. The Cosmological Standard Model is very robust and able to explain most of the features of the Cosmic Microwave Background radiation (CMB); however, when studying the different implementations of the inflationary idea, we recognize that there is, generally, a lack of connection of this physics with the low energy particle physics accessible to our experiments. This lack of connection might be because of a completely different energy scale between the inflationary processes and the low energy particle physics; thus, much more work is needed in order to connect the inflationary physics with the particle physics even for models beyond the Standard Model of Particle Physics (SM) that might operate at much higher energies. The questions we aim to answer with the development of this project are: what are the different ways of embedding cosmology into low energy particle physics, in the SM and beyond, specifically in the case that the Higgs boson(s) and the vector gauge fields play a decisive role in the cosmological implications?, and, indeed, what are those implications? To this end, and since we will be dealing with effective descriptions of different sectors of physics, we will make use of the Effective Field Theory (EFT) methodology to describe cosmological inflation.